2020
DOI: 10.1038/s41419-020-2693-8
|View full text |Cite
|
Sign up to set email alerts
|

The RBP1–CKAP4 axis activates oncogenic autophagy and promotes cancer progression in oral squamous cell carcinoma

Abstract: Retinol-binding protein 1 (RBP1) is involved in several physiological functions, including the regulation of the metabolism and retinol transport. Studies have shown that it plays an important role in the pathogenesis of several types of cancer. However, the role of RBP1 and its correlation with autophagy in oral squamous cell carcinoma (OSCC) pathogenesis remain unknown. In this study, RBP1 was identified as the most significantly upregulated DEPs with a >2-fold change in OSCC samples when compared to norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…M2 macrophage-secreted CHI3L1 could promote gastric and breast cancer metastasis [42] , and CHI3L1 modulates an immune suppressive microenvironment by reprogramming M2-like TAM in GBM [43] . TNFAIP6, RBP1, FBXO17, and GPX8 promote metastasis and invasiveness of tumor [44] , [45] , [46] , [47] . SLC43A3 and ADAM12 have been revealed as the biomarker and therapeutic target in tumor patients [48] , [49] .…”
Section: Resultsmentioning
confidence: 99%
“…M2 macrophage-secreted CHI3L1 could promote gastric and breast cancer metastasis [42] , and CHI3L1 modulates an immune suppressive microenvironment by reprogramming M2-like TAM in GBM [43] . TNFAIP6, RBP1, FBXO17, and GPX8 promote metastasis and invasiveness of tumor [44] , [45] , [46] , [47] . SLC43A3 and ADAM12 have been revealed as the biomarker and therapeutic target in tumor patients [48] , [49] .…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned, the role of autophagy in tumor development is controversial and dependent of the tumor characteristics and stage of tumor development (266). Briefly, it has been suggested that autophagy could promote aggressive characteristics of cancer cells such as increased cellular invasion (11,12), but it also represents a barrier for cancer proliferation (13)(14)(15). In cancer cells, the inhibition of autophagy results in impaired metabolism proliferation, survival, and spontaneous tumor malignancy depending not only on the tumor type but also of its temporal development (267).…”
Section: Role Of Autophagy In Vascular Remodeling In Cancermentioning
confidence: 99%
“…Indeed, the role of autophagy in tumor development is controversial and dependent on tumor stage and type. It has been suggested that autophagy could promote aggressive characteristics of cancer cells, such as increased cellular invasion (11,12), but also be a barrier to cancer proliferation (13)(14)(15). Additionally, autophagy also provides the microenvironment for placentation and cancer growth.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that RBP1 affects retinoic acid metabolism and leads to cell differentiation and tumor progression by reducing retinol transport and preventing retinol ester formation and nuclear retinoic acid receptor (RARs) activity. [ 22 ] BTC is one of the least-known ligands among endogenous EGFR ligands. BTC promotes wound healing better by promoting cell migration, but it reduces receptor affinity and attenuates the induction of EGFR phosphorylation, which is thought to be related to cancer progression.…”
Section: Discussionmentioning
confidence: 99%